Komparasi Waktu Algoritma RSA dengan RSA-CRT Base On Computer - Wibowo, Nur Cayo Hendro; Umam, Khotibul; Khaq, Albadru Muh Izul; Rizki, Favian Agung (Universitas Islam Negeri Walisongo Semarang, 2020)
Cryptography is a branch of mathematics. Asymmetric algorithms such as RSA, including the type of cryptography that is more widely used to be implemented in everyday life because it has an algorithm that is not easy to be misused by others. However, the encryption and decryption process of RSA requires quite a long time. For this reason, RSA - CRT emerged. In this study a time comparison between the RSA algorithm and the RSA-CRT Base On Computer is done. The purpose of this study was to determine the execution time of the RSA-CRT algorithm using PHP.This research uses the Research and Development or R D method, with the R D method created by the product development RSA-CRT algorithm application from UIN Walisongo Semarang based on computer. Based on the data analysis, the conclusion is that although the manual calculation of the RSA-CRT algorithm takes longer than the others in this case RSA. But have a faster time when using PHP.Â